HUBUNGAN KECEPATAN DAN KELINCAHAN TERHADAP KETERAMPILA DRIBBLING BOLA BASKET EKSTRAKULIKULER DI SEKOLAH DASAR - Fira Ashiva Nurfaida, - (2022)
ABSTRAC RELATIONSHIP OF SPEED AND AGILITY IN EXTRACURRICULAR BASKETBALL DRIBBLING SKILLS IN ELEMENTARY SCHOOL (Correlation Research On Extracurricular Members At The Sindangraja Sumedang State Elementary School) Fira Ashiva Nurfaida 1804970 This research is motivated by researchers who incidentally are basketball players, researchers know what problems exist in extracurricular members at SDN Sindangraja. The problem is the lack of speed and agility in the basketball extracurricular members of SDN Sindangraja so that it affects their dribbling skills. The method used in this research is correlation research. This research was conducted at SDN Sindangraja. With the object of research 30 extracurricular members of SDN Sindangraja. The instruments used in the study were the Slalom Dribble test and the Illinois Agility test. The results showed that there was a relationship between speed and agility with dribbling skills. This can be seen from several series of calculation techniques that researchers have done. The data analysis technique is normality test with a value of 0.016 > 0.05, the data is normally distributed. In the linearity test, it is known that the sig deviation from linearity result is 0.408> 0.05, so there is a linear relationship. Finally, the hypothesis test obtained a sig value of 0.001. Which means the value of sig 0.001 is smaller than 0.05 and it can be concluded that there is a significant relationship between speed and agility on dribbling skills in basketball extracurricular members of SDN Sindangraja. Keywords : Speed, Agility, Dribbling Skills